Towards a new philosophy of mental health: perspectives from neuroscience and the humanities - Stoyanov, Drozdstoj (Cambridge Scholars Publishing, 2015)
Machine generated contents note:ch. OneLiving at the Edge of Compromise: Balkan Pluralism as a Resource for New Philosophy of Mental Health /Drozdstoy Stoyanov --pt. IMethodology of Neuroscience Inquiry Revisited --ch. TwoCerebral Cortex Function /Wladimir Ovtscharoff --ch. ThreeEmerging Psychiatric Neuroimaging Findings: Translating the Research into Clinical Application /Drozdstoy Stoyanov --ch. FourCognitive and Brain Markers of Auditory Hallucinations in Schizophrenia /Kenneth Hugdahl --ch. FiveHughlings Jackson, Neural Connectivity and Mental Disorder /Grant Gillet --ch. SixLatent Readiness for Psychotic Symptom Formation in Individuals at High Risk for Schizophrenia: Theoretical and Practical Issues /Diana D. Shkodrova --ch. SevenClinical Applications of the Theory of Translational Validation: Potential EEG and fMRI-derived Markers of Antidepressant Treatment Response /Drozdstoy Stoyanov --pt. IIPerspectives from Psychology --ch. EightPlato's Tripartite View of the Human Psyche: Evidence from the Evolution of Human Brain Functions /C. Robert Cloninger --ch. NineThe Range of Plasticity of Personality: Implications for Identity /Ada H. Zohar --ch. TenAttachment and Personality Disorders /Vania Matanova --ch. ElevenUnderstanding Hostile Attributional Bias: Dodge's Model Revisited /Georgi Petkov --pt. IIIImplications from Phenomenology --ch. TwelveDelusional Psychosis in Early Schizophrenia: Existentialism Meets Neuroscience? /Michael A. Schwartz --ch. ThirteenThe Empathy for Pain Paradigm in Phenomenology and the Neurosciences: Where Are We? /Massimiliano Aragona --ch. FourteenCertainty -- Uncertainty: Temporal Model of Fear and Anxiety /Georgi Popov --ch. FifteenSchizophrenia, Embodiment and Intersubjectivity /Thomas Fuchs --ch. SixteenThe `What' and the `Who' in the Constitution of Psychopathological Phenotypes /Giovanni Stanghellini --Discussion --ch. SeventeenBourdieu and Stanghellini: Socioanalysis and Phenomenological Psychopathology /Todor Petkov.